Влияние изменения параметров разрядной цепи ГИТ на максимальное значение тока - Петков, Александр Александрович (НТУ "ХПІ", 2016)
В работе решена задача степенного приближения с погрешностью, не превышающей 1%, зависимости максимального значения импульса тока во всей области изменения величин параметров элементов разрядной цепи генератора импульсов тока. Полученные соотношения позволяют при любых сочетаниях значений параметров элементов разрядной цепи производить: расчеты максимальное значение импульса тока, формируемого ГИТ; определять необходимое значения одного из параметров элементов разрядной цепи ГИТ при известных значениях параметров остальных элементов и максимального значения тока, а также при модификации нагрузки. Выведены соотношения для определения проектных допусков максимального значения импульса тока.

Preparation simplified relations for determining the maximum value of the pulse current. Determination of the amount of current deviations from the nominal value in the discharge circuit of the test device. Methodology. General methodology used to determine the maximum value of the current in the high voltage generator comprising capacitive energy storage. Applying the method of approximation of functions and non-linear programming. Results. The relations that allow for any combination of values in the oscillator to produce estimates of maximum current pulse. The formulas for determining the maximum deviation of the current pulse. Originality. In this paper we solve the problem of the degree of approximation depending on the maximum value of the current pulse parameters of the discharge circuit for the entire range of their values. Approximation error does not exceed 1%. Practical value. The relations obtained allow to determine the maximum value of the current pulse; its deviation from the nominal value; diagnosis of the capacitive energy storage.
Effect of changes in the parameters of the discharge circuit CPG on the maximum current
Keywords: генератор импульсов тока; емкостной накопитель энергии; максимальное значение тока; current pulse generator; capacitive energy storage; maximum current